2018
DOI: 10.1097/md.0000000000013060
|View full text |Cite
|
Sign up to set email alerts
|

Alternative strategies to improve success rate of mitral isthmus block

Abstract: Achieving bidirectional conduction block (BDB) across the mitral isthmus (MI) is technically challenging. We describe our experience using different ablation strategies for achieving successful MI block.We reviewed the records of patients who had undergone MI ablation for peri-mitral (PM) flutter at our institution from January 2010 to May 2015. We investigated ablation strategies for achieving MI block and their long-term outcomes in terms of recurrence of atrial tachyarrhythmia.Single endocardial MI ablation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…Compared to the previous studies evaluating outcomes of the lateral MVI line ablation and/or anterior and vein of Marshall ablation [ 8 , 9 , 20 ], we successfully confirmed bidirectional block of almost all linear ablations during the first session (MVI, 96.9%; roof line, 100%). This is probably due to the fact that a considerable amount of time and RF energy was used to archive to complete the block line; however, recurrence of linear lesions was proven to some extent in the second session.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Compared to the previous studies evaluating outcomes of the lateral MVI line ablation and/or anterior and vein of Marshall ablation [ 8 , 9 , 20 ], we successfully confirmed bidirectional block of almost all linear ablations during the first session (MVI, 96.9%; roof line, 100%). This is probably due to the fact that a considerable amount of time and RF energy was used to archive to complete the block line; however, recurrence of linear lesions was proven to some extent in the second session.…”
Section: Discussionsupporting
confidence: 59%
“…Among them, linear ablation attempts to modify the left atrium (LA) as a conventional approach with proven efficacy [ 7 ]. However, creating complete (and durable) conduction block along a linear lesion is sometimes challenging [ 8 ]. In particular, ablation of the mitral valve isthmus (MVI) was achieved in 75% of patients in the Star AF II study, a large-scale randomized study [ 9 ], and the authors concluded that there was no reduction in AF recurrence when either linear ablation or CFAE ablation was performed in addition to PVI.…”
Section: Introductionmentioning
confidence: 99%
“…It is currently accepted that the creation of contiguous and transmural linear lesions across the mitral isthmus is technically challenging and may be associated with significant complications [28]. Since extensive ablation on the mitral isthmus can cause serious complications, including cardiac tamponade, circumflex artery occlusion, and atrio-esophageal fistula [29,30], increasing the RF power and ablation duration should be performed very carefully because of the increased risk of complications [31]. For this reason alternative strategies may be explored to overcome certain anatomic limitations and achieve durable mitral isthmus block, such as cryoablation [32], ethanol infusion into the vein of Marshall [33], and temporary occlusion of coronary sinus blood flow [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Venous access and catheterization were performed as previously described. 11) Transseptal catheterization was performed under the guidance of hemodynamic monitoring, fluoroscopy, and intracardiac echocardiography (SOUNDSTAR catheter; Biosense Webster, Diamond Bar, CA, USA). Two 8 Fr SL1 sheaths (St. Jude Medical, St. Paul, MN, USA) were advanced into LA to handle a mapping catheter and an ablation catheter, respectively.…”
Section: Methodsmentioning
confidence: 99%